Project management hacking how to manage projects more efficiently and effectively in less time - Martin, Douglas Peyton (Routledge/Productivity Press, 2020)
This book provides the much-needed, no-nonsense guidance crucial for project managers - that is, the type of guidance that is missing from every major body of knowledge and educational offering for working project managers. This very practical book identifies the activities that influence project success and focuses the limited time and energy available towards just those activities. The Project Management Institute (PMI) and most literature on project management discusses all aspects of project management under the assumption that project managers will narrow down focus because they cannot be expected to use every process outlined by PMI to manage every project. This book uses the concept of "hacking" our standard conventions of project management and outlines a standard path identified by conventional wisdom, an evil path that project managers frequently resort to under time/quality pressures, and a hacker path that provides a better way to look at the challenge. This book equips project managers with streamlined approaches to refocus their efforts on factors that matter while spending less time doing it. Project management is a demanding discipline with a growing body of knowledge with few instructions on how to do it all. The author provides humorous anecdotes and examples while teaching readers how to save time, improve quality, and advance their career. The primary sections of the book cover how to approach the most common certifications in project management; continuing education; leading project teams; initiating, planning, executing, monitoring, and controlling projects; general life skills; and taking on additional responsibilities. Hacking project management is about focusing the limited bandwidth a project manager can give a project towards the activities that drive success